Svetozar Marković’s and Swiss democracy - Antonic, Slobodan (Sociološki pregled, 2026)
Svetozar Marković (1846–1875) lived in Switzerland in 1869–1870 and during that time he became acquainted with the Swiss system of direct democracy, especially in the canton of Zurich. There was also a strong tradition of municipal self-government in Serbia, which was based on municipal assemblies, as a form of direct democracy. Marković wanted to reform Serbia into an association of self-governing counties, following the Swiss model. In the second step, according to Marković’s idea, the counties and the association itself would gradually begin to take on a socialist character. After the Paris Commune (1871), when Marx also accepted the idea of communalism, and especially when he agreed with the idea of a “Russian” path to socialism – with a reliance on the traditional village commune – the positions of Marković and Marx became completely close. Therefore, Marković can also be quite freely classified as a Marxist. However, since he was explicitly in favour of a democratic path to socialism (in phase two), Marković can be assessed as a Marxist-democrat.